Aspects of Leadership in The Implementation of IT Infrastructure Library Domain Service Strategy at University - Batmetan, Johan Reimon; Rawis, Joulanda A.M; Tambingon, Henny N.; Kambey, Joseph (International Journal of Information Technology and Education, 2023)
Implementation of ITIL (Information Technology Infrastructure Library) in institutions' education tall become more important for increasing the quality service of information technology. However, ITIL implementation requires a role important from leadership to ensure its success. Study This aims to analyze the role of leadership in the implementation of ITIL Service Strategy in high-education institutions. This study uses a method descriptive with do survey of IT staff at several universities. Data analyzed use the technique of qualitative and its results show that leadership owns an influence and positive significance in the implementation of ITIL Service Strategy in higher education institutions. this article gives an important view for university leadership to increase the quality service of information technology and ensure the successful implementation of the ITIL Service Strategy in institutions. This Study has implications for the organization in framework reach objective strategic in management service of information technology and ensure that ITIL framework can be used with more effective and efficient.